The Influence of The Number of Buyers, Length of Business, Type of Merchandise and The Use of E-Commerce on The Income of Kreneng Folk Market Traders in Denpasar - Wilda Br Hutabarat; Ni Nyoman Reni Suasih (Jurnal Simki Economic, 2023)
This study aims to analyze the number of buyers, length of business, type of merchandise and use of E-Commerce simultaneously and partially on the income of Kreneng Folk Market traders in Denpasar City. This research was conducted at the Kreneng Folk Market with a sample of 92 traders using the Proportional Random Sampling technique. The data used are qualitative and quantitative data. This study used multiple linear regression analysis techniques. The results showed that the number of buyers, length of business, type of merchandise and use of E-Commerce simultaneously had a significant effect on the income of Kreneng Folk Market merchants. The results of this study show that the number of buyers has a positive and partially significant effect on the income of traders in the Kreneng Folk Market. The length of business does not have a partial effect on the income of traders in the Kreneng Folk Market. Traders who sell types of basic food merchandise have an income that is not higher than traders who sell types of non-staple food merchandise at the Kreneng Folk Market. Merchants who use E-Commerce have a higher income than merchants who do not use E-Commerce at the Kreneng Folk Market.